2016
DOI: 10.1038/srep32251
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Comparison of Two Densely Sampled HIV Epidemics: The UK and Switzerland

Abstract: Phylogenetic clustering approaches can elucidate HIV transmission dynamics. Comparisons across countries are essential for evaluating public health policies. Here, we used a standardised approach to compare the UK HIV Drug Resistance Database and the Swiss HIV Cohort Study while maintaining data-protection requirements. Clusters were identified in subtype A1, B and C pol phylogenies. We generated degree distributions for each risk group and compared distributions between countries using Kolmogorov-Smirnov (KS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 31 publications
9
11
1
Order By: Relevance
“…The high proportion of DRMs associated with infrequently used ART regimens combined with the clustering of many TDR strains suggests that some proportion of TDR strains represent established drug-resistant lineages transmitted among ART-naive individuals. This hypothesis is consistent with findings from other countries with mature HIV-1 epidemics such as Switzerland and the United Kingdom, where it has been estimated that most TDR cases are transmitted from ART-naive individuals [34, 36, 38, 39]. Our dataset, however, is limited by the fact that KPNC provides care to about 25% of the insured population in Northern California [12], making it likely that many transmission events occurred with individuals not within our cohort and not captured in our phylogenetic analyses.…”
Section: Discussionsupporting
confidence: 91%
“…The high proportion of DRMs associated with infrequently used ART regimens combined with the clustering of many TDR strains suggests that some proportion of TDR strains represent established drug-resistant lineages transmitted among ART-naive individuals. This hypothesis is consistent with findings from other countries with mature HIV-1 epidemics such as Switzerland and the United Kingdom, where it has been estimated that most TDR cases are transmitted from ART-naive individuals [34, 36, 38, 39]. Our dataset, however, is limited by the fact that KPNC provides care to about 25% of the insured population in Northern California [12], making it likely that many transmission events occurred with individuals not within our cohort and not captured in our phylogenetic analyses.…”
Section: Discussionsupporting
confidence: 91%
“…Although a source of uncertainty is the lack of risk factor information for a large part of our cohort, the consistency of our findings in different analyses suggest an important role of MSM living in Lisbon for this sub-epidemic. These results are consistent with other studies in Europe, Brazil or USA, where young MSMs have been identified as the main drivers of subtype B and TDR transmission [35,7]. More studies are needed to evaluate how tourism or migration may influence these results.…”
Section: Discussionsupporting
confidence: 90%
“…Transmission cluster reconstruction has been previously used to understand HIV-1 and resistance transmission patterns in other settings [37]. Herein, we combine and compare the information provided by classical statistical analyses of the most complete Portuguese cohort available, stratified by subtypes, with the one retrieved from transmission clusters analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This percentage is at the higher end of figures reported for comparable populations [4,[30][31][32][33][34][35][36][37]. A one-to-one comparison of these studies is however hampered by differences in time period, depth of sampling, geographical region, degree of heterogeneity of the studied population, and lack of uniformity in methods and definition [38]. In our population for instance, marked differences were observed between the patients of Belgian origin and the patients of African origin.…”
Section: Discussioncontrasting
confidence: 52%